2019
DOI: 10.1111/jfb.14084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predator exposure on baseline and stress‐induced glucocorticoid hormone concentrations in pumpkinseedLepomis gibbosus

Abstract: We compared baseline and maximal cortisol concentrations between predator exposure and prey blood samples in pumpkinseed Lepomis gibbosus, captured using a standardised fishing event underneath osprey Pandion haliaetus nests and away from osprey nests. We did not detect differences in cortisol or glucose between sites.These findings suggest that predictable sources of predation risk may not confer stress-related costs in teleosts. FISHdirectly overhead, etc.), may signal fish to mount an anti-predator behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Acknowledging that many maternal steroids play a role in offspring development and can vary in a coordinated fashion within eggs, will help us move beyond the focus on maternally derived glucocorticoid steroids 2,38,77 . That we did not see a consistent pattern of predation regime on steroid profiles was unexpected (but see 78 ), particularly given the role of glucocorticoids in dealing with predator encounters 2,14,79 , as well as the findings that stress-induced cortisol levels can be sensitive to rearing conditions 80 , heritable 80,81 , and respond to selection 82 . Not only is there no obvious difference between lakes with and without predatory trout, but exposure to piscine predators for 25 or fewer generations (stocked lakes) and ~6,000 generations (native lakes) have similar consequences for the steroid profiles.…”
Section: Discussionmentioning
confidence: 80%
“…Acknowledging that many maternal steroids play a role in offspring development and can vary in a coordinated fashion within eggs, will help us move beyond the focus on maternally derived glucocorticoid steroids 2,38,77 . That we did not see a consistent pattern of predation regime on steroid profiles was unexpected (but see 78 ), particularly given the role of glucocorticoids in dealing with predator encounters 2,14,79 , as well as the findings that stress-induced cortisol levels can be sensitive to rearing conditions 80 , heritable 80,81 , and respond to selection 82 . Not only is there no obvious difference between lakes with and without predatory trout, but exposure to piscine predators for 25 or fewer generations (stocked lakes) and ~6,000 generations (native lakes) have similar consequences for the steroid profiles.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, hormonal implants causing a long-term moderate elevation of corticosterone levels in mountain chickadees (Poecile gambeli) enhance food caching behaviour and spatial memory, important fitness traits for these birds as successful cache retrieval can be crucial for survival (Pravosudov 2003). Additionally, although predation risk is often associated with increased glucocorticoid levels in prey, some studies have also reported no association between predator regimes and cortisol levels (Gallagher, et al 2019, McGhee, et al 2020, highlighting the complexity of the link between predation risk, stress hormones, and cognitive performance. In our study, predation risk reduced performance in the simple associative learning task, which could be consistent with a "nonadaptive" scenario predicting detrimental effects of stress on cognition (Lupien, et al 2009, Piato, et al 2011, Sapolsky 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of predators stresses captive and wild fish [63][64][65] and may negatively affect immunocompetence, metabolism and growth in salmonids and other fish, 66,67 especially during critical life stages such as smoltification. 27 Because these potential effects are being likely, we found no quantitative evidence relating pinniped attacks or presence around salmon farms with increased fish susceptibility to diseases, reduced growth rates or any other related productive loss.…”
Section: Other Potential Adverse Effectsmentioning
confidence: 99%